FAKTOR-FAKTOR YANG MEMPENGARUHI PENGHINDARAN PAJAK (Studi Empiris Pada Perusahaan Manufaktur yang Terdaftar di BEI 2015-2017) - Nova Agustin K.W, 15.05.52.0068; Wahyudi, Djoko (Students' Journal of Accounting and Banking, 2019)
This study aims to determine and analyze the influence of the application of board of independent commissioners, audit committee, leverage, return on assets and firm size to tax avoidance. The population and this study focused on companies listed on the Indonesia Stock Exchange (IDX) for the 2015-2017 period. Data collection techniques using purposive sampling, so that there are a total sample of 180 companies and data analysis using multiple linear regression analysis. In this study the independent variables use board of independent commissioners, audit committee, leverage, return on assets, and the size of the company that will affect tax avoidance as a dependent variable that is proxied through Effective Tax Rates (ETR). The results of the analysis show that board of independent commissioners has no significant effect on tax avoidance, audit committee, negatively has a significant effect on tax avoidance, leverage has a positive effect on tax avoidance, return on assets has a negative negative effect on tax avoidance, and company size has a negative and insignificant effect on tax avoidance.